2021
DOI: 10.3390/foods10102505
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of an Aglycone-Enhanced Celery Extract with Germinated Soy Supplementation Using Response Surface Methodology

Abstract: In this study, the extraction conditions of bioactive aglycones from a celery extract supplemented with germinated soy were optimised by a response surface methodology. For subsequent enzymatic hydrolysis to enhance the apigenin content, increased production of its precursor apigetrin was firstly achieved through acidic extraction at optimal conditions, involving water at pH 1, at 75 °C for 2 h. Subsequently, a central composite design was conducted to analyse the pH (3–11) and temperature (25–35 °C) effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Celery, (family Apiaceae) has long been acknowledged for its special aroma and flavor, as well as its non-digestible carbohydrates, such as dietary fiber and oligosaccharides, which are presently considered prebiotics because they reach the colon undigested, where they are fermented mainly by bifidobacteria and lactic acid bacteria, thus producing a conclusive health effect that is gently and incompletely absorbed from the small intestine, while it can also be considered a potential prebiotic ingredient of functional foods, such as mannitol (Rupérez and Toledano, 2003). Comparably, celery is widely conceded as a functional food that encourages the prevention, management and regulation of chronic diseases by many consumers (Arsenov et al, 2021;Lau et al, 2021). Investigation has revealed that celery water extract can destroy viruses and inhibit their replication (Gaballah et al, 2020), showing therapeutic actions that are strongly linked to plant antioxidant status (Kharchenko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Celery, (family Apiaceae) has long been acknowledged for its special aroma and flavor, as well as its non-digestible carbohydrates, such as dietary fiber and oligosaccharides, which are presently considered prebiotics because they reach the colon undigested, where they are fermented mainly by bifidobacteria and lactic acid bacteria, thus producing a conclusive health effect that is gently and incompletely absorbed from the small intestine, while it can also be considered a potential prebiotic ingredient of functional foods, such as mannitol (Rupérez and Toledano, 2003). Comparably, celery is widely conceded as a functional food that encourages the prevention, management and regulation of chronic diseases by many consumers (Arsenov et al, 2021;Lau et al, 2021). Investigation has revealed that celery water extract can destroy viruses and inhibit their replication (Gaballah et al, 2020), showing therapeutic actions that are strongly linked to plant antioxidant status (Kharchenko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%